Justice at the Margins: Reclaiming Gender Equality Amid Structural Injustice in Indonesia’s Palm Oil Plantations - Damayanti, Cicilia; Isharianto, Rafael (Studia Philosophica et Theologica, 2025)
This paper examines the pervasive gender-based injustices faced by women and children working in Indonesia’s palm oil plantations. It explores how structural inequalities manifest through economic exploitation, limited access to basic services, and systemic marginalization. Drawing on the philosophical frameworks of Nancy Fraser and Serene J. Khader, the study employs a normative and conceptual methodology, integrating Fraser’s tripartite model of justice—redistribution, recognition, and representation—with Khader’s theory of adaptive preferences and localized empowerment. The analysis demonstrates that achieving gender equality in this context requires both structural reform and context-sensitive empowerment strategies. As a practical contribution, the paper proposes the development of a mobile community initiative, Pos Kesetaraan, which embodies both theoretical approaches by delivering legal, educational, and health-related support directly to marginalized laborers. The findings suggest that without sustained, multi-scalar interventions, justice will remain inaccessible to the most vulnerable. Ultimately, the paper argues for a reconceptualization of development practices in the palm oil sector, calling for urgent ethical commitment and political action to restore dignity and equity to the lives of plantation workers